Design of Talent Acquisition System Based on Individual Development Plan in Human Resources Management - Prasetyo, Wahyu Eko; Ambarwati, Rita; Fitriyah, Hadiah (Almana : Jurnal Manajemen dan Bisnis, 2023)
The shift in the concept of a human resources-based workforce management system for human capital provides a new discourse that employee development programs should be compiled comprehensively through a detailed system from the Manpower Procurement Planning Process, Selection, to the Employee development process and along their career. This study aims to design and describe talent acquisition design based on the principle of individual development. The research design uses a qualitative design that focuses on the field of research & and development that focuses on the talent acquisition applied system development model and is integrated based on the principle of an individual development plan. They start with scope identification, GAP Analysis, Requirement Analysis, System Literature Study, System Integration and design, and end with a group discussion forum. The results of this research resulted in a design to develop a talent acquisition system that is oriented towards individual development. This system is a combination of many approaches that correlate with the stages of talent management, so the procedure for implementing talent acquisition is not only about HR recruitment but also the management and development of HR competencies and careers.